A Comment on Dincecco et al. (2022): Pre-Colonial Warfare and Long-Run Development in India - Rachel Forshaw; Tim Ölkers; Ritika Sethi; Manali Sovani (Institute for Replication (I4R), 2023)
We test the reproducibility and replicability of Dincecco et al. (2022), which reports a positive relationship between pre-colonial interstate warfare and long-run development patterns across India. Overall, we confirm that all of the study's estimates are computationally reproducible by using both the provided replication package in Stata and code written by the present authors in R. We test for and find no evidence of data manipulation in the final datasets. Concerning direct replicability, we consider different ways of measuring distance to conflicts and also alternative proxies for both the dependent variable and variables which capture channels by which the main effects operate. We are able to replicate the magnitude and significance of the estimated coefficient on conflict exposure in most of the tests, noting that while most estimates are substantively in line with the original study, some alternative measures of distance to conflict imply different magnitudes for estimates, and proxy estimates are sensitive to both the time period and type of conflict considered.
Keywords: H11; N45; O11; P48; 330; institutions; long-run development; path dependence; public goods